PRELIMINARY ESTIMATION OF EMISSION FACTORS FOR MOTORCYCLES IN REAL-WORLD TRAFFIC CONDITIONS OF HANOI - Thu, Ta Huong; Tuan, Le Anh; Dung, Nghiem Trung (Vietnam Journal of Science and Technology, 2012)
ABSTRACTThis paper presents a method to estimate emission factors of motorcycles based on the local driving cycle and modal emissions measured in the laboratory. This method was developed to reflect real-world motorcycle traffic conditions of Hanoi, Vietnam as well as to correspond to the economical - technical infrastructure of Vietnam. Applying into the estimation of emission factors of four selected air pollutants of motorcycles including HC (hydrocarbons), CO (carbon monoxide), CO2 (carbon dioxide) and NOx (as NO), the following results were obtained: 1.109 (g/km), 11.355 (g/km), 43.971 (g/km) and 0.124 (g/km), respectively. These emission factors are a significant contribution to Vietnam database of emission factors that are still scarce. Emission factors obtained in this study would also help improve the accuracy of emission models and emission inventories, which plays an important role in air quality management and traffic planning of Hanoi, Vietnam.